Experience, facilitators, and barriers to the implementation of a multicomponent programme in older people living in the community, +AGIL Barcelona: A qualitative study - Canet-Vélez, Olga; Solis-Navarro, Lilian; Sitjà-Rabert, Mercè; Pérez, Laura Mónica; Roca, Judith; Soto-Bagaria, Luis; Torres-Castro, Rodrigo; Díaz-Gallego, Francisco; Vilaró, Jordi; Inzitari, Marco (Frontiers in Public Health, 2023)
Introduction: The +AGIL Barcelona programme is a multi-component care intervention for frail older adults (FOA) living in the community. To improve the programme, it is essential to investigate the experience of all participants. Our objective was to explore the perspective of FOA and professionals about the barriers, facilitators and improvements elements of the development of the +AGIL Barcelona programme. Qualitative descriptive approach. We included FOA and professionals who participated in the +AGIL Barcelona programme. Methods: Three focus groups and four interviews were conducted. These were analysed following the qualitative method of content analysis. The criteria of scientific rigour of credibility, dependence and transferability were ensured throughout the study. Results: Three themes and seven sub-themes were developed: Facilitators (positive experience, perceived benefits), barriers (self-perceived health status, digital divide, continuity of the programme at home) and improvements elements (programme continuity and adaptation of technology). All the participants felt satisfied, highlighting aspects such as interpersonal relationships and social contact, face-to-face sessions guided by a physiotherapist and the functional improvement achieved. Some of the difficulties were the self-perception of frailty, the need for technological support, and continuing the exercise programme at home. Conclusion: The FOA who participated in the +AGIL Barcelona programme perceived direct benefits for their health and physical condition due to the development of self-confidence by being able to perform physical exercise despite their baseline condition, and the professionals experienced an improvement in the quality of care due to work in a multidisciplinary team.